Implementasi Bauran Pemasaran Pada Production House ZH Picture (Program Studi Ilmu Administrasi Bisnis, 2022)
Service marketing is a marketing that cannot be seen but can be felt. Services must prioritize the convenience of service to consumers. Services cannot be returned like finished goods. The marketing mix is ​​a set of products, prices, places, promotions, processes, people and physical evidence. The marketing mix is ​​used to measure the level of marketing success and all of it is aimed at getting the response that consumers want. The marketing mix is ​​a tool used by sellers to shape the characteristics of the services offered to customers. Production house is a service business that is engaged in fields such as photo and video content creator, design, content writer, audio visual that has an organizational structure. Production houses provide displays of their productions to the general public either directly or broadcasting. Production House in managing motion or static information where information can be sourced from humans or existing events. ZH Picture is a Production House in Jember which is engaged in photo and video making services such as weddings, company profiles, and product advertisements. The level of success is measured by the company ZH Picture by using the marketing mix of goods and services and creating innovation.